Platform Gamifikasi untuk Perkuliahan - David Kristiadi; Khabib Mustofa (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2017)
Gamification in lecturing has a lot of variety designs. A flexible platform is needed for that matter. This research aims to develop a gamification platform for lecturing that flexible, has a good performance and acceptable by users.Generic Gamification Platform (GGP) concept is used to develop platform. GGP is a kind of gamification solution that applies service oriented architecture Architecture (SOA) principles and puts gamification components (data, logic and rewards) and Information System (IS) separately. The platform has some capabilities such as able to manage game mechanics, actions, tasks and rules. The other platform capabilities are able to auto generate rules and to be integrated to IS.The results of tests show that a gamification platform for lecturing can be developed. The platform has a good level of flexibility, has a good performance, and acceptable by users (5 lecturers and 2 non-lecturers but well knowing on lecturing activities). Its flexibility level is 85%. Its average of response time on event execution is lower than 336ms. Its System Usability Scale (SUS) average score is 60 and its acceptability range in low marginal.